Structural Behaviour of Load-Bearing Interlocking Hollow Block Masonry - Najm, Amad M. S. (2001)
The structural behaviour of an interlocking block system has been investigated in this research. The interlocking blocks developed by the Housing Research Center, Universiti Putra Malaysia have been used to assemble a number of prisms and wall panels. This interlocking block system has been filed for a patent. Three types of individual blocks are utilized in this research, these are stretcher, comer and half block units. I The research covers the production of the block using a manually controlled machine which has been developed for the production of the three different types of block. The test program includes testing of individual blocks, prisms and different wall panels. Forty individual blocks have been tested under axial compression. Ten prisms have been tested under axial1oad. The failure mechanism were recorded for each type of specimen. Sixteen wall specimens having different height (slenderness ratio), subjected to load applied at different eccentricities, have been tested. The selected heights of the tested walls are 1.2, 1.8, 2.4 and 3.0m. The eccentricity of the applied load is another important parameter considered in testing the wall specimens to simulate the actual nature of the applied load in construction. The values are 0, 20, 40 and 55mm measured from the centerline of the wall panels. The structural behaviour of the wall panel specimens were studied in terms of the load-deflection characteristic, strain-stress distribution, efficiency of the wall and the failure mode of the interlocking walls. The study focuses on the differences and similarities of the behaviour of interlocking walls compared to bonded walls. BS 5628: Part 1: 1978 was used to explore the behaviour of the bonded walls. The study showed that the strength of the interlocking block and its interlocking mechanism were sufficient and that the block can be used for construction of load bearing walls. Based on the test results, a number of mathematical equations have been proposed to predict the reduction in the wall efficiency with the increases of the eccentricity of the applied load and the slenderness ratio of the wall. A design procedure has also been proposed to be used in the design of load bearing interlocking hollow block system.